2016
DOI: 10.1111/iji.12248
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐A, HLA‐B, HLADRB1 allele and haplotype frequencies of 14 529 Chinese Han bone marrow donors living in Dalian, China

Abstract: We investigated the allele and haplotype frequencies of HLA-A, HLA-B and HLA-DRB1 loci in Dalian Chinese Han population using blood samples of unrelated marrow donors who live in Dalian. The genetic relationship between Dalian and different regions worldwide was further explored based on HLA status of different populations. A total of 14,529 samples were genotyped at 2-digit level only by sequence-specific oligonucleotide and sequence-based typing methods. Allele frequencies of HLA-A, HLA-B and HLA-DRB1 were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“…8 For example, in populations living in latitudes higher than that of Shanghai, the A*30-B*13-DRB1*07 frequency was found to be higher than that of A*02-B*46-DRB1*09; the converse was seen in populations living in lower latitudes. 9 In this case, the patient was a native of Beijing which lies at a higher latitude than Shanghai, and his HLA haplotype was consistent with the above regional distribution. Although the positivity rates of HLA-DRB1*07:01 and HLA-DQB1*02:02 antibodies in Chinese donors do not classify them as high-frequency antibodies (about 0.2%), 10 the risk of TRALI is high due to the high proportion of corresponding HLA genotypes; the Chinese Common Allele (CWD) catalog lists the frequencies of the HLA-DRB1*07:01 and HLA-DQB1*02:02 genotypes as 9.3% and 7.4%, respectively.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…8 For example, in populations living in latitudes higher than that of Shanghai, the A*30-B*13-DRB1*07 frequency was found to be higher than that of A*02-B*46-DRB1*09; the converse was seen in populations living in lower latitudes. 9 In this case, the patient was a native of Beijing which lies at a higher latitude than Shanghai, and his HLA haplotype was consistent with the above regional distribution. Although the positivity rates of HLA-DRB1*07:01 and HLA-DQB1*02:02 antibodies in Chinese donors do not classify them as high-frequency antibodies (about 0.2%), 10 the risk of TRALI is high due to the high proportion of corresponding HLA genotypes; the Chinese Common Allele (CWD) catalog lists the frequencies of the HLA-DRB1*07:01 and HLA-DQB1*02:02 genotypes as 9.3% and 7.4%, respectively.…”
Section: Discussionsupporting
confidence: 70%
“…In Chinese donors, the most frequent HLA‐A‐B‐C‐DRB1‐DQB1 haplotype is A*30:01‐B*13:02‐C*06:02‐DRB1*07:01‐DQB1*02:02 (37‰), with the frequency of this haplotype varying in different regions of China, decreasing gradually from northeast to southwest 8 . For example, in populations living in latitudes higher than that of Shanghai, the A*30‐B*13‐DRB1*07 frequency was found to be higher than that of A*02‐B*46‐DRB1*09; the converse was seen in populations living in lower latitudes 9 . In this case, the patient was a native of Beijing which lies at a higher latitude than Shanghai, and his HLA haplotype was consistent with the above regional distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, there were many reports available on the HLA‐A, HLA‐B and HLA‐DRB1 distribution in the Chinese populations (He et al, ; Li et al, ; Pei, Huang, Li, Chen, & Wu, ; Shao et al, ; Wang et al, ), but data on AFs and HFs of HLA‐C and HLA‐DQB1 are limited in Zhejiang Han population. In this study, we firstly reported the distribution of AFs and HFs of HLA‐A, HLA‐B, HLA‐C, HLA‐DRB1, and HLA‐DQB1 loci in Zhejiang Han population at a high‐resolution level.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the results showed that HLA‐A*33:03~B*58:01~DRB1*03:01 is the most common haplotype in the Nanning Han population, which is similar to the southern Chinese population and southern East Asia populations (Ding et al, ; He et al, ; Hoa et al, ; Lai et al, ; Shi et al, ). However, HLA‐A*30:01~B*13:02~DRB1*07:01 is the most frequent haplotype in the north Han populations but less common in the Nanning Han population (Li et al, ; Shao et al, ). In fact, it just reflects the general north–south genetic differentiation observed in many studies focusing on HLA alleles (Di & Sanchez‐Mazas, ) or other genetic markers, especially for markers on Y chromosomes and mitochondrial DNA (mtDNA; Zhang, Su, Zhang, & Jin, ).…”
Section: Discussionmentioning
confidence: 99%